Face recognition for remote database backup system - Mohamed Din, Aniza; Ahmad, Faudziah; Mohamad Mohsin, Mohamad Farhan; Ku-Mahamud, Ku Ruhana; Theab, Mustafa Muwafak (2011)
Face recognition is one of the most interesting applications in the image processing field.To build a model to recognize the face of different people, we need to do several processes on the image to obtain the most efficient features.In this research a face recognition model is developed.The dataset used is of different face images. Neural Networks technique, specifically Multilayer Perceptron (MLP) model with Back-Propagation learning algorithm and Template Matching approach are implemented in model developed.The face recognition model developed is then applied on a remote database backup system.Template matching approach is found to give a higher percentage of matching accuracy and a faster result can be obtained compared to MLP as no learning process is required